1997
DOI: 10.1007/s004649900561
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laparoscopy on the movement of tumor cells and metastasis to surgical wounds

Abstract: Carbon dioxide insufflation results in tumor dissemination during laparoscopy, leading to port site metastasis. Gasless laparoscopy may prevent this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 13 publications
(45 reference statements)
0
34
0
2
Order By: Relevance
“…As suggested by few animal studies, the port-site incision is more conducive than the laparotomy incision for tumor seeding. 19 Aoki et al 20 suggest that repair of the peritoneum at the trocar entry site may reduce the risk of tumor implantation and subsequent recurrence. Immune depression of the peritoneum occurs during laparoscopic insufflation as demonstrated by macrophage function alteration, resulting in tumor recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by few animal studies, the port-site incision is more conducive than the laparotomy incision for tumor seeding. 19 Aoki et al 20 suggest that repair of the peritoneum at the trocar entry site may reduce the risk of tumor implantation and subsequent recurrence. Immune depression of the peritoneum occurs during laparoscopic insufflation as demonstrated by macrophage function alteration, resulting in tumor recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A cytology sampling was obtained, which did not influence therapeutic decisions. Mean exploration time was 22 minutes (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). If the tumor was considered curable, the trocars were withdrawn and a laparotomy and radical gastrectomy were performed.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, studies have been addressed concerning the influence of laparoscopy on tumor spreading and patient survival. They suggest a role for CO 2 diffusion (16)(17)(18)(19)(20)(21)(22), limited surgeon experience and consequent tumor handling (21,23), direct cell adhesion to ports (24), trocar material composition (25), and hematogenous spread (26,27). At present controversy persists.…”
Section: Introductionmentioning
confidence: 99%
“…35,37 There have been contradictory reports on the role of the pneumoperitoneum as the cause of port site metastasis and carcinomatosis. [38][39][40] In an novel study by Ikramuddin et al, carbon dioxide effluent recovered from patients with cancer during laparoscopy was examined. 40 The authors concluded that malignant cells are aerosolized in laparoscopic surgery, but in patients without carcinomatosis, aerosolization is unlikely to contribute to port site metastasis.…”
Section: Surgical Management Of Adrenal Metastasismentioning
confidence: 99%